2020
DOI: 10.3390/molecules25194398
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Intake and Physical Activity: Associations with the Lipid Profile of a US Working Population

Abstract: While growing evidence exists on the independent associations between anthocyanins and physical activity on cardiovascular disease (CVD) risk determinants, the possible interaction between these exposures has not yet been studied. We aimed to study the potential synergism between anthocyanin intake and physical activity on lipid profile measures. This cross-sectional study was conducted among 249 US career firefighters participating in the Feeding America’s Bravest trial. Anthocyanin intake was calculated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…BMI was recorded for all study subjects in kg/m 2 from measured height and weight. Body fat (%) was estimated by a Bioelectrical Impedance Analyzer (BIA) [40,45].…”
Section: Outcome Assessmentsmentioning
confidence: 99%
“…BMI was recorded for all study subjects in kg/m 2 from measured height and weight. Body fat (%) was estimated by a Bioelectrical Impedance Analyzer (BIA) [40,45].…”
Section: Outcome Assessmentsmentioning
confidence: 99%
“…Finally, it is also shown that anthocyanins have vasorelaxant, antihypertensive, antihemolytic activities and attenuate platelet aggregation [1]. The inverse relationship between anthocyanins intake and the total cholesterol:high density lipoprotein (HDL) cholesterol levels was also observed in the cross-sectional study carried out by Hershey et al [4] and published in this issue. Furthermore, the joint effect of a low anthocyanin intake and low physical exercise more than doubled the relative risk of having HDL cholesterol<40 mg/dL, compared to high anthocyanins/high activity joint exposure, although the results lack statistical significance [4].…”
mentioning
confidence: 73%
“…Research has suggested that greater adherence to the Mediterranean diet has substantial inverse correlation with risks for heart disease and diabetes, LDL cholesterol, and weight gain, and is associated with higher HDL cholesterol [ 20 , 25 , 49 ]. A recent study found that high intakes of anthocyanins (polyphenols found in red, blue, and purple foods) increase HDL cholesterol, suggesting that it may have cardioprotective effects [ 28 ]. While this study lost statistical significance in its multivariable models, it does provide significant implications for future studies.…”
Section: Resultsmentioning
confidence: 99%
“…While this study lost statistical significance in its multivariable models, it does provide significant implications for future studies. Based on their results, Hershey et al [ 28 ] also indicate that the Mediterranean diet, which is rich in polyphenols, can increase anthocyanin intake.…”
Section: Resultsmentioning
confidence: 99%